A COL5A2 In-Frame Deletion in a Chihuahua with Ehlers-Danlos Syndrome - Sarah Kiener; Lucie Chevallier; Vidhya Jagannathan; Amaury Briand; Noëlle Cochet-Faivre; Edouard Reyes-Gomez; Tosso Leeb (Genes, 2022)
Ehlers-Danlos syndrome (EDS) is a group of heterogeneous, rare diseases affecting the connective tissues. The main clinical signs of EDS are skin hyperextensibility, joint hypermobility, and skin fragility. Currently, the classification of EDS in humans distinguishes 13 clinical subtypes associated with variants in 20 different genes, reflecting the heterogeneity of this set of diseases. At present, variants in three of these genes have also been identified in dogs affected by EDS. The purpose of this study was to characterize the clinical and histopathological phenotype of an EDS-affected Chihuahua and to identify the causative genetic variant for the disease. The clinical examination suggested a diagnosis of classical EDS. Skin histopathology revealed an abnormally thin dermis, which is compatible with classical EDS. Whole-genome sequencing identified a heterozygous de novo 27 bp deletion in the COL5A2 gene, COL5A2:c.3388_3414del. The in-frame deletion is predicted to remove 9 amino acids in the triple-helical region of COL5A2. The molecular analysis and identification of a likely pathogenic variant in COL5A2 confirmed the subtype as a form of classical EDS. This is the first report of a COL5A2-related EDS in a dog.